Carbon-nutrient stoichiometry drives phosphorus immobilization in phototrophic biofilms at the soil-water interface in paddy fields. (15th December 2019) - Liu, Junzhuo; Sun, Pengfei; Sun, Rui; Wang, Sichu; Gao, Bo; Tang, Jun; Wu, Yonghong; Dolfing, Jan
Abstract: Phototrophic biofilms are distributed widely at the sediment/soil-water interfaces (SWI) in paddy fields, where they immobilize phosphorus, thereby reducing its runoff loss. However, how soil carbon, nutrient availability and nutrient ratios drive the phototrophic biofilm community and its contribution to phosphorus cycling is largely unknown. A large scale field investigation in Chinese paddy fields reported here shows that soil organic carbon (SOC) and soil total nitrogen (STN) contents rather than soil total phosphorus (STP) triggered phosphorus immobilization of paddy biofilms, as they changed algal diversity and EPS production. High C: P and N: P ratios favored phosphorus immobilization in biofilm biomass via increasing the abundance of green algae. The C: N ratio on the other hand had only a weak effect on phosphorus immobilization, being counteracted by SOC or STN. Results from this study reveal how the in-situ interception of phosphorus in paddy fields is driven by soil carbon, nutrient availability and nutrient ratios and provide practical information on how to reduce runoff losses of phosphorus by regulating SOC and STN contents. Graphical abstract: Image 1 Highlights: Soil organic carbon, nitrogen, C/P and N/P are central in driving P immobilization. Soil organic carbon and nitrogen counteract the effect of C/N on P immobilization. Green algae and extracellular polymeric substances are vital in P immobilization.